½-homogeneous hyperspaces - Macias, Sergio (Topology Proceedings, 2021)
Sam B. Nadler, Jr. and Patricia Pellicer-Covarrubias studied the $\frac{1}{2}$-homogeneity of the hyperspace of subcontinua of a continuum $X$. We continue this investigation and include results about the $\frac{1}{2}$-homogeneity of the hyperspace suspension of $X$.